2021
DOI: 10.3892/mmr.2021.12205
|View full text |Cite
|
Sign up to set email alerts
|

Long non‑coding RNA XIST promotes cerebral ischemia/reperfusion injury by modulating miR‑27a‑3p/FOXO3 signaling

Abstract: Cerebral ischemia/reperfusion (I/R) injury leads to neuronal damage, which may cause disability and even mortality. Multiple studies have revealed that long non-coding RNAs (lncRNAs) serve pivotal roles in the pathogenesis of cerebral I/R injury. Therefore, the present study aimed to investigate whether the lncRNA X inactivate-specific transcript (XIST) protects neuronal cells from cerebral I/R injury. In the present study, reverse transcription-quantitative PCR demonstrated that XIST expression was upregulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…CI is a major threat to human health, which can lead to brain injury, disability, and even death worldwide [ 20 ]. The principle of TCM treatment of CI is to promote blood circulation and remove stasis, while acupuncture-moxibustion can not only improve blood circulation but also relieve muscle spasm of patients and enhance limb mobility [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…CI is a major threat to human health, which can lead to brain injury, disability, and even death worldwide [ 20 ]. The principle of TCM treatment of CI is to promote blood circulation and remove stasis, while acupuncture-moxibustion can not only improve blood circulation but also relieve muscle spasm of patients and enhance limb mobility [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another recent study reported that expression of the lncRNA Neat1 was significantly decreased in OGD/R-induced BV-2 and N2a cells compared with that in control cells ( Zhou et al, 2022 ). The lncRNA XIST was also reported to be highly expressed in an MCAO/R-treated animal model and an OGD/R-treated cell model ( Zhang et al, 2021d ; Wang et al, 2021 ; Xiong et al, 2021 ). Wang et al also reported that the lncRNA XIST was upregulated in brain tissues under MCAO/R treatment and in OGD/R-treated PC12 cells ( Wang et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Xiong et al found that XIST was significantly highly expressed in SH-SY5Y cells after OGD/R treatment ( Xiong et al, 2021 ). Finally, another study identified that XIST expression was upregulated in the brain tissues of an I/R mouse model and OGD/R-induced N2a cells ( Zhang et al, 2021d ). The findings of these previous studies are in accordance with our results, indicating the robustness of our analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reperfusion of ischemic tissue through thrombolysis and interventional therapy can be used to treat ischemic stroke through embolized cerebral vascular recanalization, but this treatment method is associated with ischemia reperfusion injury (IRI) (Chen et al, 2016). IRI may result in neuronal damage that can lead to brain dysfunction and even death (Zhang et al, 2021). Moreover, not all patients with acute ischemic stroke could benefit from reperfusion therapies based on inclusion/exclusion criteria (Hern andez et al, 2021).…”
Section: Introductionmentioning
confidence: 99%